Loss of susceptibility to complement lysis in Entamoeba histolytica HM1 by treatment with human serum. - Calderon, J (1986)
Entamoeba histolytica HM1, exposed to a series of treatment with normal human serum (NHS), progressively lost susceptibility to complement lysis. Trophozoites were incubated daily with unheated or heat-inactivated NHS for 2 hr at 36 degrees, starting with 10% v/v serum and increasing by 5% every 3 days up to 40% NHS. Resistance to complement lysis was also obtained with two different HM1 clones but not with the low virulent strain HK9. Induction of resistance dependent on the number of NHS treatments, with a maximal 50% reduction occurring after 11 treatments. Susceptibility to complement-dependent lysis was regained 6 weeks after serum treatments were terminated, suggesting that resistance to lysis was an acquired rather than a genetic property.